0731 Factors Affecting Pediatric Adherence to Positive Airway Pressure: Treatment Barriers, Sleep Difficulties, and Behavioral Sleep Medicine Consultation. (12th April 2019) - Carmody, Julia K; Simakajornboon, Narong; Gurbani, Neepa; Burrows, Carolyn; Krietsch, Kendra; Graef, Danielle; Byars, Kelly C
Abstract: Introduction: Nonadherence to positive airway pressure therapy (PAP) limits treatment effectiveness for obstructive/central sleep apnea (O/CSA). One-third of pediatric patients fail to use PAP as prescribed; children demonstrate variable night-to-night use and inadequate within-night use, often <50% of expected sleep period. We evaluated predictors of PAP adherence and the feasibility/impact of behavioral sleep medicine consultation (BSMC) provided during a multidisciplinary CPAP clinic. Methods: Retrospective chart review of 106 patients (ages 2-29 [M=14.5±5.4]; 39% female, 25% Black/African-American) prescribed PAP. PAP adherence assessed via objective download/smartcard; patients/caregivers completed the Pediatric Barriers to CPAP Questionnaire (PBCQ; Simon, 2011) and Pediatric Insomnia Severity Index (PISI; Byars, 2017). Linear regression was used to examine predictors of PAP adherence. Results: At initial BSMC (T1), frequency of PAP use was 70.7±32.7% of nights observed and duration was 5.9±3.2 hours/night worn. Nightly PAP use of ≥ 4 hours occurred on 56.0±36.8% of nights observed. Linear regression showed that worse sleep onset problems (PISI) predicted worse PAP adherence (frequency; duration; % nights ≥ 4 hours) and that more treatment barriers (PBCQ) significantly predicted worse adherence. Linear regression also demonstrated that youth-reported behavioral and cognitive/affective barriers (e.g., "I can be healthy without PAP") and parent-reported behavioral barriers (e.g., "My child stops using PAP during the night") predicted worse adherence. Participants receiving BSMC demonstrated improved adherence at T2 (75.7% nights, 6.21 hours/night worn) and at T3 (75.9% nights, 6.6 hours/night worn), although changes were not statistically significant. Conclusion: Preliminary results demonstrate feasibility of integrating BSMC into pediatric multidisciplinary O/CSA care. Subjective reports of sleep onset difficulty as well as behavioral, affective and cognitive PAP treatment barriers predicted poorer adherence. Adherence trends improved following BSMC, however current findings are tentative due to limited sample size at follow-up intervals. Findings highlight the importance of evaluation and treatment of patient/caregiver reported sleep disturbance and PAP barriers in the context of pediatric care for O/CSA. Future directions include ongoing examination of the clinical effectiveness of BSMC on adherence and sleep quality over time. Support (If Any): NIH T32HD068223